2011
DOI: 10.4061/2011/219189
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Breast Cancer Metastasis to the Brain

Abstract: Our knowledge of the biology underlying the development of brain metastases (BM) from breast cancer has improved over the last decade due to large clinical epidemiological studies, animal models of metastasis, and the use of high-resolution gene expression profiling technologies. However, there are still major gaps in our understanding of the mechanisms utilized by breast cancer cells to colonize the brain microenvironment, thus our arsenal of therapies remains relatively nonspecific, and the prognosis for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Approximately 10-16% of breast cancer patients develop brain metastases, and this continues to be a major cause of mortality in women [1,2,4,5]. The mean survival of patients with brain metastases ranges from 3–18 months, with a one-year survival rate of 20% [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10-16% of breast cancer patients develop brain metastases, and this continues to be a major cause of mortality in women [1,2,4,5]. The mean survival of patients with brain metastases ranges from 3–18 months, with a one-year survival rate of 20% [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease with respect to molecular features, which is perhaps best exemplified by the molecular subgroups identifiable by gene expression profiling including basal-like, luminal A (hormone receptor positive), luminal B, and human epidermal growth factor receptor 2 (HER2) amplified/over-expressed (HER2+) subtypes (Saunus et al, 2011). It has been demonstrated that primary breast cancer with a basal-like immunophenotype has the propensity to metastasize to the brain (Espinosa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The most common primary metastatic sites in adults are the lung (35%), central nervous system (CNS; 25-30%) and breast (14-18%; Weil et al, 2005;Cambruzzi et al, 2011;Saunus et al, 2011). This phenomenon is called organotropism, which means that the distribution of metastasis in different organs is nonrandom; i.e., the tumor cells could have specific affinity for the microenvironments of certain organs (Talmadge and Fidler, 2010;Saunus et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations